2021
DOI: 10.46497/archrheumatol.2021.8625
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of potential biomarkers and therapeutic targets for systemic sclerosis-associated interstitial lung disease

Abstract: Objectives: This study aims to analyze gene expression in lung tissue and lung fibroblasts of patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD) to identify potential biomarkers and therapeutic targets and to examine its possible role in the pathogenesis of SSc-ILD. Patients and methods: We obtained datasets from Gene Expression Omnibus (GEO) database, and used Robust Rank Aggregation to calculate the co-expressed differentially-expressed-genes (DEGs) in three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(70 reference statements)
1
0
0
Order By: Relevance
“…IL1 is produced by monocytes and macrophages,and consists of two forms,IL-1A and IL-1B,which exert proin ammatory effects by binding to the IL-1 receptor [25,26] .Clinical studies have found that in the acute exacerbation stage of COPD,the level of IL-1B in the sputum of patients was notably higher compared with control group,and the NF-kB signaling pathway of macrophages was also markedly activated [27] .Surprisingly,these studies were consistent with the results of our analysis that IL1B may regulate the function of macrophages via necroptosis signaling pathway.The concept of dendritic cells are regulators that link innate and adaptive immunity has long been well established.Our analysis showed that IL1B was positively correlated with dendritic cells and Th17 cells,these results are in line with experiment research conclusion from the expression of IL1B in dendritic cells preferentially induces Th17 cell differentiation [28] .Besides,the presence of IL1B signaling pathway in dendritic eclls can be used as an accelerator of their ability to induce T cell activation,or IL1B can also directly regulate CD4+ and CD8+ T cells [29] .NKT cells can bind to Fas receptors on the surface of bone marrow-derived dendritic cells via Fas ligands,prompting the release of IL1B [30] .By RT-qPCR,we also observed increased mRNA expression level of IL1B in CSE-treated BEAS-2B cells.The tumor necrosis factor-α(TNF-α) inducer 3 gene encodes TNFAIP3,which has been implicated in the development of chronic in ammation in COPD [31] ,and interstitial lung disease is associated with systemic sclerosis [32] .Our experimental study also nd evidence of increased expression of TNFAIP3 under cigarette snoke exposure.…”
Section: Discussionsupporting
confidence: 55%
“…IL1 is produced by monocytes and macrophages,and consists of two forms,IL-1A and IL-1B,which exert proin ammatory effects by binding to the IL-1 receptor [25,26] .Clinical studies have found that in the acute exacerbation stage of COPD,the level of IL-1B in the sputum of patients was notably higher compared with control group,and the NF-kB signaling pathway of macrophages was also markedly activated [27] .Surprisingly,these studies were consistent with the results of our analysis that IL1B may regulate the function of macrophages via necroptosis signaling pathway.The concept of dendritic cells are regulators that link innate and adaptive immunity has long been well established.Our analysis showed that IL1B was positively correlated with dendritic cells and Th17 cells,these results are in line with experiment research conclusion from the expression of IL1B in dendritic cells preferentially induces Th17 cell differentiation [28] .Besides,the presence of IL1B signaling pathway in dendritic eclls can be used as an accelerator of their ability to induce T cell activation,or IL1B can also directly regulate CD4+ and CD8+ T cells [29] .NKT cells can bind to Fas receptors on the surface of bone marrow-derived dendritic cells via Fas ligands,prompting the release of IL1B [30] .By RT-qPCR,we also observed increased mRNA expression level of IL1B in CSE-treated BEAS-2B cells.The tumor necrosis factor-α(TNF-α) inducer 3 gene encodes TNFAIP3,which has been implicated in the development of chronic in ammation in COPD [31] ,and interstitial lung disease is associated with systemic sclerosis [32] .Our experimental study also nd evidence of increased expression of TNFAIP3 under cigarette snoke exposure.…”
Section: Discussionsupporting
confidence: 55%